HUBUNGAN ANTARA KEGIATAN BERMAIN BENDA ALAM TERHADAP KEMAMPUAN MENGENAL ANGKA ANAK USIA DINI (PENELITIAN DI KELOMPOK B1 RA AL-WAFI PANYILEUKAN KOTA BANDUNG): THE RELATIONSHIP BETWEEN NATURAL MATERIALS PLAY ACTIVITIES AND NUMBER RECOGNITION ABILITY IN EARLY CHILDHOOD (A STUDY IN GROUP B1 RA AL-WAFI PANYILEUKAN, BANDUNG CITY) - Nurfitriyani, Nurfitriyani; Kurnia, Aam; Syamiyah, Syamiyah (Universitas Islam Malang, 2022)
Research to find out the reality of playing natural objects. Natural objects can be used to recognize numbers. This research was conducted in group B1 RA Al- Wafi Panyileukan Bandung City. The research method is correlational. The research subjects were the children of group B1 RA Al-Wafi Panyileukan Bandung City in the 2018/2019 Academic Year, totaling 18 children. The results of the analysis were 84 from the interval 80 – 100. very good category. The ability to recognize numbers for early childhood can get an average value of 76. This number is in the 70-79 interval with a good category. the correlation coefficient through the Spearman Rank formula (ρ_count) is 0.71. This correlation coefficient is included in the strong category at the interval 0.600-0.799. The results of the significance test obtained t_count = 4.0329 the price of t_table = 2.120. This means that the null hypothesis is rejected and the alternative hypothesis is accepted. Playing natural objects has a significant positive relationship with the ability to recognize numbers in Group B1 RA Al-Wafi Panyileukan Bandung City. The contribution/influence of playing natural objects on the ability to recognize early childhood numbers is 50.41%. there are other factors 49.59% that affect the ability to recognize early childhood numbers.